PHA RMA COE CONOMI CAL EVALUATION OF MULTIPLE MYELOMA TREATMENT WITH REVLIMID (LENALIDOMIDE ) IN THE RUSSIAN FEDE RATION - R. Yagudina; A. Kulikov; B. Misikova (Фармакоэкономика)
Pharmacoeconomic evaluation of treatment of the second and third lines of multiple myeloma with Revlimid in Russia was conducted. It has shown, that application of lenalidomide as a drug of choice in the treatment of multiple myeloma in second-line therapy and is preferable from the perspective of the health economics.